The school building as the "embodiment of non-sustainability": Education for Sustainable Development in the school space (Pedagogical Horizons, 2023)
In this article, spatial sociological perspectives are linked to the implementation of Education for Sustainable Development. The focus is on the question to what extent the school building as a school space influences the teachers' possibilities of action with regard to the teaching of sustainability topics. The core of the contribution are selected results of a qualitative-reconstructive study, for which 20 group discussions with teachers were conducted and analysed with the help of the documentary method. It is shown that the school space is perceived by the teachers as either very conducive or inhibiting for the implementation of sustainability topics. Finally, the results are discussed in terms of transformational educational processes and in relation to a whole-institution approach.
Keywords: Education for sustainable development, school space, qualitative-reconstructive research, Whole Institution Approach